Pre‐adaptation to climate change through topography‐driven phenotypic plasticity. (28th February 2020) - De Kort, Hanne; Panis, Bart; Helsen, Kenny; Douzet, Rolland; Janssens, Steven B.; Honnay, Olivier
Abstract: Climate change will increase the level of drought stress experienced by plant communities, but the spatial distribution of projected changes in dryness remains highly uncertain. Species can, to some extent, deal with climate uncertainty through natural variation in adaptive responses to environmental heterogeneity and predictability. Biodiversity conservation could thus target populations pre‐adapted to climatic heterogeneity to anticipate climate uncertainty. Disentangling adaptive evolution of trait means versus trait plasticity, however, requires a sampling design with genetic replicates grown under distinct environmental conditions. Here, we applied three soil moisture treatments to genetic replicates of Fragaria vesca plants raised from seeds that were sampled in distinct topographical settings, to study adaptive trait and plasticity divergence in response to drought. We demonstrate that various plant traits evolved along distinct topographical gradients. Populations on south‐exposed slopes, for example, retained high levels of both flowering and runner formation under drought stress, while north‐faced populations hardly flowered under reduced soil moisture levels. Aspect but not elevation was found to coincide with variation in plant traits, suggesting that microenvironmental variation rather than general clines in elevation drive evolution in mountainous landscapes. Our results also indicate that traits and their plasticity can evolve independently in response to distinct topographical stressors. Synthesis . We conclude that heterogeneous landscapes (a) harbour micro‐refugia of adaptive genetic diversity that protect natural populations against environmental change, and (b) represent invaluable sources of quantitative genetic variation that could support conservation where climate projections are inconclusive. Abstract : We conclude that heterogeneous landscapes (a) harbour micro‐refugia of adaptive genetic diversity that protect natural populations against environmental change, and (b) represent invaluable sources of quantitative genetic variation that could support conservation where climate projections are inconclusive.